Sunflower house - Bunting, Eve, 1928-; Hewitt, Kathryn (San Diego : Harcourt Brace, 1996)
A young boy creates a summer playhouse by planting sunflowers and saves the seeds to make another house the next year.
Elem. School Library Collection, June 2000.
School Library Journal, May 1996.
Book Links (A.L.A.), October 2000.
Booklist, April 1996.
Horn Book, September 1996.
2.8.
Keywords: Sunflowers -- Fiction; Stories in rhyme; Sunflowers -- Fiction; Stories in rhyme; Sunflowers -- Fiction; Stories in rhyme